2019
DOI: 10.1158/1535-7163.mct-18-0196
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Enhances the Therapeutic Effects of Oxaliplatin by Upregulating BIM in Colorectal Cancer

Abstract: Despite an increase in the survival rate of patients with cancer owing to the use of current chemotherapeutic agents, adverse effects of cancer therapies remain a concern. Combination therapies have been developed to increase efficacy, reduce adverse effects, and overcome drug resistance. Genipin is a natural product derived from Gardenia jasminoides, which has been associated with anti-inflammatory, anti-angiogenic, and anti-proliferative effects; hypertension; and anti-ischemic brain injuries. However, the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…IHC was carried out as previously described [41]. The tissue was observed by confocal microscopy (ZEISS-LSM 700, ZEISS, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…IHC was carried out as previously described [41]. The tissue was observed by confocal microscopy (ZEISS-LSM 700, ZEISS, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Genipin (GP) is an alternative to currently used chemical- and physical-based collagen crosslinking agents. GP is a naturally occurring organic crosslinking agent derived from gardenia plant (Gardenia jasminoides), which has been used in Chinese medicine for its anti-carcinogenic, anti-angiogenic, and neuroprotective properties [ 41 , 42 , 43 , 44 ]. Compared to other chemical crosslinking agents, GP has many advantages including being a natural crosslinking agent, the stability and biocompatibility of the crosslinked products, and low toxicity [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study, we found that genipin enhanced oxaliplatin-induced apoptosis in colorectal cancer 22. In our study, we investigated whether genipin enhanced oxaliplatin induced cell death for gastric cancer.…”
Section: Discussionmentioning
confidence: 89%